1ISG-037 Health-related quality of life in hepatitis c patients who achieve sustained virological response to direct-acting antivirals: a comparison with the general population. (March 2019) - Juanbeltz, R; Castilla, J; Martínez-Baz, I; O'Leary, A; Burgui, C; Preciado, J; Ulacia, L; Larrayoz, B; Sarobe, M; San Miguel, R
Abstract : Background: A short-term benefit on health-related quality of life (HRQoL) has been reported in successfully treated chronic hepatitis C patients with direct-acting antivirals. However, no information exists regarding the HRQoL difference compared to the general population after viral clearance. Purpose: To compare HRQoL outcomes between hepatitis C patients who achieve sustained virological response (SVR) and a sample of the general population. Material and methods: Patients were recruited from May 2016 to April 2017. At post12 SVR time-point, a hospital pharmacist assessed HRQoL using the EQ-5D-5L questionnaire in a telephone interview. Results were compared to those of the general population of the same sex and age obtained from the 2011/12 National Health Survey in Spain. Observed/expected (O/E) ratios for health dimensions (mobility, self-care, usual activities, pain/discomfort and anxiety/depression) and differences between O/E in EQ-5D utility and visual analogical scale (VAS) scores were calculated. Results: Two-hundred and six patients with SVR were studied. Mean age was 52 (SD=9.0) years. Sixty-six per cent were male and 32% were HIV co-infected. According to liver fibrosis, 25% were F0–F1, 47% F2–F3% and 28% cirrhotic. After SVR, patients had more limitation than the general population, especially for the usual activities (O/E=3.1), anxiety/depression (O/E=2.8) and EQ-5D utility (−0.086, p<0.001): however, no difference in VAS score was observed (74.8 vs 76.5 respectively, p=0.210). F0–F1 patients with SVR had minor differences with the general population in mobility (O/E=0.6), self-care (O/E=1.0), usual activities (O/E=1.5) and pain/discomfort (O/E=1.3). However, anxiety/depression was nearly three times more frequent compared to the general population (O/E=2.7). Cirrhotic patients still had worse HRQoL after SVR, especially in usual activities (O/E=4.8) and self-care domains (O/E=3.7), EQ-5D utility values (−0.152, p<0.001) and VAS score (−8.5, p=0.005). Conclusion: HRQoL of chronic hepatitis C patients is considerably lower than that of the general population despite SVR. Knowledge of ongoing problems serves to guide the patient's follow-up. Monitoring mental health in patients with low fibrosis stage, and the assessment of the ability to undertake usual activities and self-care in patients with cirrhosis should be recommended in the post-treatment setting. References and/or acknowledgements: EIPT-VHC project funded by the Spanish Ministry of Health and Carlos III Institute of Health. Conflict of interest: Corporate-sponsored research or other substantive relationships: Regina Juanbeltz has received funding from the Carlos III Institute of Health with the European Regional Development Fund (CM17/00095).